Development and Characterization of Buccal Film: Tacrolimus as A Model Drug - P, Ashwathy; R, Arjun; R, Raghavi; Anil, Anjitha; A Surendran, Saritha (Journal of Medical Biomedical and Applied Sciences, 2019)
Buccal drug delivery has become a relevant route of administration. It has got various advantages, masking the firstpass metabolism being the primary one, thus ensuring increased drug bioavailability at the site of action. Tacrolimus,an immunosuppressant, calcineurin inhibitor is the drug of choice. Oral tablet suffers from high first pass metabolismand topical formulations such as ointments readily washout from the site of application. Tacrolimus formulated asmucoadhesive buccal film provided prolonged effect than topical formulations. Films (F1 & F2) were prepared bysolvent casting technique. Chitosan being the best mucoadhesive polymer with wound healing properties increased theretention time of the film at the wound site. HPMC ensured good film property. Propylene glycol was used as plasticizerand citric acid as salivary stimulator and cross linker. The compatibility of drug in the formulation was confirmed byFTIR. Formulated films were subjected to various evaluation parameters, and all the physical parameters were withinthe acceptable limits. In vitro release was found to be better for F1. Ex vivo studies of F1 using goat mucous showed apermeation of 76.5%.